CD4(+) T Cells Which React to the Leishmania major LACK Antigen Rapidly Secrete Interleukin-4 and Are Detrimental to the Host in Resistant B10.D2 Mice - Julia, Valérie (American Society for Microbiology, 1999)
Leishmania major induces the rapid production of interleukin-4 (IL-4) in both susceptible BALB/c and resistant B10.D2 mice. In both strains, IL-4 is produced by T cells which react to the parasite LACK (for Leishmania homolog of the receptor for activated C kinase) antigen. The rapid production of IL-4 in B10.D2 mice does not confer susceptibility but results in increased parasite burdens.